Deciphering the Crucial Roles of the Quorum-Sensing Transcription Factor SdiA in NADPH Metabolism and (S)-Equol Production in Escherichia coli Nissle 1917 - Zhe Wang; Yiqiang Dai; Fidelis Azi; Mingsheng Dong; Xiudong Xia (MDPI AG, 2024)
The active metabolite (S)-equol, derived from daidzein by gut microbiota, exhibits superior antioxidative activity compared with its precursor and plays a vital role in human health. As only 25% to 50% of individuals can naturally produce equol when supplied with isoflavone, we engineered probiotic E. coli Nissle 1917 (EcN) to convert dietary isoflavones into (S)-equol, thus offering a strategy to mimic the gut phenotype of natural (S)-equol producers. However, co-fermentation of EcN-eq with fecal bacteria revealed that gut microbial metabolites decreased NADPH levels, hindering (S)-equol production. Transcriptome analysis showed that the quorum-sensing (QS) transcription factor SdiA negatively regulates NADPH levels and (S)-equol biosynthesis in EcN-eq. Screening AHLs showed that SdiA binding to C10-HSL negatively regulates the pentose phosphate pathway, reducing intracellular NADPH levels in EcN-eq. Molecular docking and dynamics simulations investigated the structural disparities in complexes formed by C10-HSL with SdiA from EcN or E. coli K12. Substituting sdiA_EcN in EcN-eq with sdiA_K12 increased the intracellular NADPH/NADP+ ratio, enhancing (S)-equol production by 47%. These findings elucidate the impact of AHL-QS in the gut microbiota on EcN NADPH metabolism, offering insights for developing (S)-equol-producing EcN probiotics tailored to the gut environment.